2021
DOI: 10.3390/foods10061296
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Isolate Microgel Properties Tuned by Crosslinking with Organic Acids to Achieve Stabilization of Pickering Emulsions

Abstract: Whey protein isolate (WPI) can be used effectively to produce food-grade particles for stabilizing Pickering emulsions. In the present study, crosslinking of WPI microgels using organic acids (tannic and citric acids) is proposed to improve their functionality in emulsions containing roasted coffee oil. It was demonstrated that crosslinking of WPI by organic acids reduces the microgels’ size from ≈1850 nm to 185 nm and increases their contact angle compared to conventional WPI microgels, achieving values as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…tannic acid. 99 Resulting modified WPMs provided a more effective adsorption at O/W interfaces than conventional WPMs, although still possessing a rather hydrophilic polymer structure. In addition, their particle size and distribution were smaller than those of conventional WPM microgels.…”
Section: Applications Of Microgels With Hydrophobic Domainsmentioning
confidence: 96%
“…tannic acid. 99 Resulting modified WPMs provided a more effective adsorption at O/W interfaces than conventional WPMs, although still possessing a rather hydrophilic polymer structure. In addition, their particle size and distribution were smaller than those of conventional WPM microgels.…”
Section: Applications Of Microgels With Hydrophobic Domainsmentioning
confidence: 96%
“…Crosslinking WPM particles with organic acids, such as citric and tannic acid, has been shown to produce smaller, less polydisperse particles that also appeared to offer a better emulsion stability compared to conventional WPM stabilised emulsions. 105 …”
Section: Proteins In Pickering Emulsionsmentioning
confidence: 99%
“…The rigid structure in its spatial conformation is considered to be the basis for its application in food processing [ 2 ]. In general, food proteins can act as good foaming agents to give foam-based foods a satisfying appearance, taste, and texture, such as ice cream, angel cake, and salad dressings [ 3 ]. However, under the diverse environmental conditions of food processing, thermally unstable protein foam systems are not very stable [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a simple and efficient foam stabilization technique may be beneficial to solve this problem. Recently, several teams have found that microparticles formed from biomacromolecules might possess excellent interfacial stabilization [ 3 , 11 ]. Protein microgels and starch granules have been shown to be embedded at the air-water interface under specific conditions to achieve stability of the foam system [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation